Metaphorical Modeling of Laughter and Crying Situations in Uzbek and English - qizi, Azimova Muxtasarxon Jaloldin; qizi, Mirzayeva Gulasal Ulug’bek (Journal of Innovation in Education and Social Research, 2024)
This study explores metaphorical modeling of laughter and crying situations in Uzbek and English, focusing on how these expressions reflect cultural perspectives, emotions, and experiences. Metaphors associated with laughter and crying convey nuanced emotional states and social functions within each language, providing insight into shared human experiences as well as distinct cultural frameworks. By examining metaphorical phrases and idioms in both languages, the study aims to illustrate the similarities and differences in how laughter and crying are linguistically represented. The analysis reveals that while some metaphors are universal, reflecting common emotional experiences, others are unique to specific cultural contexts, shaped by historical, social, and linguistic factors. This comparative approach offers a deeper understanding of how metaphor serves as a bridge between language and emotion across cultures.